Traqueotomía quirúrgica y su incidencia en las complicaciones infecciosas en pacientes de la unidad de cuidados intensivos del Hospital IESS Babahoyo - Los Ríos octubre 2019 – marzo 2020. - Mora Aguiar, Diana Maribel (2020)
The introduction of the current research paper tells us that worldwide airway management is a primary point in the Intensive Care Unit and in the emergency areas, the main objective of this surgical intervention is to maintain adequate tissue oxygenation of the patient , as a general objective we have: “To determine the complications of surgical tracheotomy occur in patients of the intensive care unit of the IESS Babahoyo- Los Ríos Hospital October 2019 - March 2020”, the research is Historical with a qualitative approach, not experimental, within of the results we can state that of the late complications, the ones that had the greatest relevance were infections of all kinds with 60%, to solve the problem raised it is necessary to apply a proposal which is entitled “Information guide for the care of the airway in tracheotomized patients in the intensive care unit of the IESS Babahoyo ”, the objective of this proposal is to Unify criteria for the care of patients with tracheotomy of the intensive care unit of the IESS Babahoyo hospital.